The Application of Natural Dyes in Food Freshness Indicators Designed for Intelligent Packaging - Tichoniuk, Mariusz; Radomska, Natalia; Cierpiszewski, Ryszard (Studia Oeconomica Posnaniensia, 2017)
The paper presents natural dyes i.e. curcumin, grape peel and beetroot extract which were incorporated into the compositions of food freshness indicators. The obtained indicators were assessed and compared with an artificial dye, methyl red, in relation to their capability of volatile amine monitoring. Additionally, a model of volatile amine release based on the evaporation of ammonia solution was applied in the first stage of the presented research. The response of freshness indicators was estimated by the colorimetric analyses of colour alteration and the calculation of Total Colour Difference (TCD) index values. Comparing to the methyl red dye, the grape peel extract gave a similar response with the TCD value equalled ca. 30 units. Beetroot extract did not provide a desirable colour change and the most promising composition was the indicator containing the curcumin addition. Further research was made on the freshness indicators containing only curcumin, grape peel extract or methyl red. The indicators were evaluated in relation to their response to the spoilage of raw cod flesh both in the model system (chamber with evaluated indicators) and in food packaging (plastic box). Although all examined natural dyes were able to detect food spoilage, the response comparable to the methyl red was obtained for grape peel extract in the model system and for curcumin in a real package. Both natural dyes and methyl red provided the colour changes correlated with cod flesh spoilage and characterized with TCD values equal to ca. 30 units.